Los estudiantes Universitarios Javerianos y su respuesta al sentido de la vida - Jaramillo, Alba Liliana (2022)
The purpose of this study was to identify the aspects which have a significant influence on the meaning of life for psychology students between 16 and 34 years old at the Pontificia Universidad Javeriana, Cali. The instrument used to gather the information was the A. Langle and C. Orgler existential test, a technical instrument consisting of 46 items, divided into four sub groups: self-distancing, self-transcendence, freedom, and responsibility. The sample was made up of 277 students, 60 men and 217 women, ranging from first to tenth semester. The results show that the scores obtained were below average for all the variables (age, gender, and semester) with a total score of 177.83 for the total scale, which means that the meaning of life is placed at a low level, without significant differences for any of the variables relating to the meaning of life.